Femmes de mœurs légères au XVIIe siècle - Charbonneau, Hubert (Mémoires de la Société généalogique canadienne-française, 1996)
Lien avec Montréal -- énumération de femmes bannies ou autres pour des moeurs légères. Petite analyse.
Keywords: Femmes

Table ronde. L'histoire des femmes: 25 ans de recherche et d'enseignement - Baillargeon, Denyse (Cahiers d'histoire, 1996)
Keywords: Femmes; Histoire

Menstruation Goes Public: Aspects of Women's Menstrual Experience in Montreal, 1920-1975 - Armeni, Elizabeth (Université McGill, 1996)
Keywords: Femmes

Roughing It In Suburbia: Reading Chatelaine Magazine 1950-1969 - Korinek, Valerie Joyce (University of Toronto, 1996)
Keywords: Femmes; Féminisme

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Keywords: Femmes; Université McGill

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Criminal Women and Bad Girls: Regulation and Punishment in Montreal, 1890-1930 - Myers, Tamara (Université McGill, 1996)
Keywords: Criminalité; Délinquance; Femmes; Prisons

Antiracism organizing and resistance in nursing : African Canadian Women - Calliste, Agnes (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1996)
Keywords: Africains; Femmes; Infirmières; Noirs

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Étude du processus de construction du sens dans les médias: le cas de la tragédie de l'École polytechnique en 1989 - Boudreau, Julie (Université de Sherbrooke, 1996)
Keywords: Devoir (Le); Femmes; Montreal Gazette; Presse (La); École polytechnique